2019
DOI: 10.5004/dwt.2019.24186
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of Cr(VI) using biochar-supported Cu/Fe bimetallic nanoparticles

Abstract: Nanoscale zero-valent iron (nZVI) has been proven to be more effective for the treatment of hexavalent chromium(Cr(VI)) when modified with the transition metal Cu. In this study, biochar-supported Cu/Fe bimetallic nanoparticles (Cu-nZVI/BC) were prepared and used for Cr(VI) removal from aqueous solution. The effects of the pH value, the initial concentration of Cr(VI), coexisting ions and humic acids (HA) were investigated. The compositional structures of Cu-nZVI/BC were analyzed by transmission electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…A diffraction peak at 50.4° was observed in the pattern of Cu/Fe bimetallic nanoparticles, which indicated that (200) facet of fcc copper (JCPDS no. 04–0836) was loaded on the surface of the particles 27 . In addition, the bimetallic nanoparticles after reaction with Cr(VI) was analyzed by XRD patterns (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A diffraction peak at 50.4° was observed in the pattern of Cu/Fe bimetallic nanoparticles, which indicated that (200) facet of fcc copper (JCPDS no. 04–0836) was loaded on the surface of the particles 27 . In addition, the bimetallic nanoparticles after reaction with Cr(VI) was analyzed by XRD patterns (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the presence of these ions could compete for the reaction sites on the surface of the iron particles 47 . On the other hand, certain ions (such as Ca 2+ ) could result in nZVI aggregation and reduce the removal efficiency 27 . Moreover, the solution pH was alkaline (pH = 8.32 ± 0.10), which inhibited the reaction of Cu/Fe nanoparticles with Cr(VI) under high pH conditions 48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the modified Langmuir isotherm model assumes that each site can bind a single adsorbate molecule, and there is no interaction between two adsorbed pollutant molecules. Also, the modified Langmuir model implies that adsorption processes are controlled by chemical reactions 29 , 70 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the Langmuir isotherm model assumes that each site can bind a single adsorbate molecule, and there is no interaction between two adsorbed pollutant molecules. Also, the Langmuir model indicates that adsorption processes are controlled by chemical reactions 16,49 . The changes in Cr concentration (total Cr, Cr(VI), and Cr(III)) in aqueous solution during reaction time using Talc-nZVI/6Sn was illustrated in Fig.…”
Section: Adsorption Isotherm Analysismentioning
confidence: 99%